Analysis of the Direction of the NTB Provincial Government's Policy in Employment Development - Amil, Amil; Rifaid, Rifaid; Hidayatullah, Hidayatullah; Hadi, Ayatullah; Abdurrahman, Abdurrahman (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
The purpose of this study is to determine the West Nusa Tenggara (NTB) Provincial Government's policy in implementing strategic policies in workforce development. The main focus of this policy includes reducing unemployment, creating harmonious industrial relations, and developing productive transmigration areas. This study uses a comparative descriptive method with a qualitative approach and uses library research to obtain secondary data. The results of the study indicate that in 2022, the number of workers in NTB will reach 2.79 million people, with 2.71 million of them already employed, so that the unemployment rate will decrease to 2.98 percent, exceeding the RPJMD target of 3.17 percent. However, with the addition of more than 50 thousand new workers each year, a special strategy is needed to create more jobs. The NTB Manpower and Transmigration Office has established six strategic steps to overcome unemployment, including workforce planning, improving human resource competency through vocational training, workforce placement and empowerment, social protection for workers, workforce development and supervision, and implementation of presidential regulations regarding the Integrated Plus Workforce Training and Empowerment Program (PePaDu Plus).